Recommendations for the Best Contract Labor Handling Staff Using the Complex Proportional Assessment Method - Adi Widarma; Dharyana Suryadijaya; Bagus Rizki Lubis; Ira Murni (CESS (Journal of Computer Engineering, System and Science), 2023)
Staff or commonly referred to as employees are an important part of a company/institution, especially those who have the quality and enthusiasm to maintain the progress of the agency. The purpose of this research is to find out decision making or problem solving in determining the best contract staff recommendations at SERGAI DISPORAPARBUD so that later these staff can be more motivated in their performance. To conduct this research, observational research methods, interviews and literature studies were carried out and the calculation process was carried out using the COPRAS method. In addition to determining the best contract labor recommendations, several criteria must be met by each alternative, namely discipline, honesty, communication, cooperation, and responsibility. The results of this study indicate that 10 alternatives get the top ranking, one of which is a staff named Jaliya SE with a utility value of 100 getting the first rank in the recommendation to become the best contract worker at DISPORAPARBUD SERGAI.